Mem as a tool of information war - Smola, Lidia (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2019)
It is devoted to the problem of analyzing memes as a tool of information warfare. The article analyzes the history and origin of the study of memes as a phenomenon of information interaction and social technology. Memes can be interpreted as: image, idea, symbol, action, any cultural information copied by one person from another; the collective unconscious at the moment of acquiring verbal and visual form; specially created information message, which is distributed in the information space and is intended to form the necessary picture of the human world and make appropriate decisions. The meme influences the perception of reality and drives action. Different types, types of memes and their characteristics are considered. There is a diversity of spread of this phenomenon: global Internet memes, understandable to a wide range of people, and local memes that require specific awareness (gaming, hacking, scientific, professional). Emphasis is placed on the use of memes in contemporary armed conflicts. The information war, combined with the peculiarities of the modern information society, led to the use of new technologies to influence the mass consciousness, in particular, memetic weapons. The article analyzes memetic weapons as a technology of using memes for the distribution of beneficial information in the information space of the object of information confrontation. Particular attention was paid to the analysis of the perceptions of memes by ATO participants and volunteers. The urgency of the problem is determined by the need to analyze the impact of ideas reflected in Internet memes on the mass consciousness during the Russo-Ukrainian war. Within the framework of the Polish-Ukrainian project "Crisis Intervention – Support for NGOs in Ukraine Working with ATO Soldiers and Their Families", 20 flexible interviews were conducted. The focus of the study may be to analyze the perception and functioning of political Internet memes on social media. Empirical studies of the influence of Internet memes on the structural components of the psyche of Internet users are also promising. The war in eastern Ukraine reaffirmed the paradigm shift of modern warfare, demonstrated the thoroughness of a thorough study of the phenomenon and the need to develop entirely new approaches to the realization of political and military goals.